Genome-Wide Survey of SNP Variation Uncovers the Genetic Structure of Cattle Breeds - Gibbs, Richard A.; Taylor, Jeremy F.; Van Tassell, Curtis P.; Barendse, William; Eversoie, Kallye A.; Gill, Clare A.; Green, Ronnie D.; Hamernik, Debora L.; Kappes, Steven M.; Lien, Sigbjorn; Matukumalli, Lakshmi K.; Murdoch, Brenda; et al. (Amer Assoc Advancement Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.